2017
DOI: 10.1186/s13045-016-0369-8
|View full text |Cite
|
Sign up to set email alerts
|

Indirect treatment comparison of dabrafenib plus trametinib versus vemurafenib plus cobimetinib in previously untreated metastatic melanoma patients

Abstract: BackgroundMetastatic melanoma is an aggressive form of skin cancer with a high mortality rate and the fastest growing global incidence rate of all malignancies. The introduction of BRAF/MEK inhibitor combinations has yielded significant increases in PFS and OS for melanoma. However, at present, no direct comparisons between different BRAF/MEK combinations have been conducted. In light of this, an indirect treatment comparison was performed between two BRAF/MEK inhibitor combination therapies for metastatic mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 28 publications
4
34
0
Order By: Relevance
“…Enhanced MEK activity can cause abnormal activation in the RAS-RAF-MEK-ERK pathway, which has been reported to be responsible for the pathogenesis of inflammation and approximately 30% of all human malignancies [4,5]. Thus, MEK has been the target of various drug discoveries [6][7][8][9][10][11][12][13][14], and inhibition of MEK activity may be used to treat MEK pathway activation-driven cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced MEK activity can cause abnormal activation in the RAS-RAF-MEK-ERK pathway, which has been reported to be responsible for the pathogenesis of inflammation and approximately 30% of all human malignancies [4,5]. Thus, MEK has been the target of various drug discoveries [6][7][8][9][10][11][12][13][14], and inhibition of MEK activity may be used to treat MEK pathway activation-driven cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The strategy of combining BRAFi and MEKi with immunotherapy requires a better understanding of the effects of kinase inhibition on normal immune cell function. Although the two currently approved combinations of BRAFi and MEKi appear similarly effective against melanoma [ 28 ], their effects on healthy cells, not bearing BRAF mutations, but employing the respective signaling pathway, may significantly differ. BRAFi have for example a paradoxical effect on wild-type BRAF [ 29 ], which is more pronounced for Vem than for Dabra [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The opportunity for cross‐trial comparison is very interesting, but interpretation of results from an HRQoL perspective is challenging and should be done cautiously. For example, Daud, Gill, Kamra, Chen, and Ahuja () performed a comparison of efficacy and safety results between the COMBI‐v and coBRIM trials that showed a better safety profile for dabrafenib plus trametinib compared with vemurafenib plus cobimetinib, an observation that does not necessarily translate into a difference in HRQoL outcomes. The blinded or unblinded nature of a trial's design can also greatly impact the perception of benefit and thus comparisons between trials with open‐label and double‐blind designs should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 99%